Ultra-late relapse of acute promyelocytic leukemia 18 years after complete remission: a case report and literature review - Gao, Lu; An, Yang; Li, Qian; Shi, Shuo; Zhou, Jie; Du, Zuochen; Huang, Pei; Ren, Mingqiang; Chen, Yan (Frontiers in Medicine, 2025)
Late relapse of acute promyelocytic leukemia (APL) is associated with high mortality rates. While APL typically shows a low incidence of relapse after achieving complete remission (CR) for more than 7 years, we report a rare case of APL relapse occurring 18 years after CR was achieved. The patient was successfully treated with a combination of arsenic trioxide (ATO) and all-trans retinoic acid (ATRA), leading to favorable outcomes. Additionally, we review our treatment experience and provide a comprehensive analysis of the existing literature, summarizing the characteristics of reported APL cases that relapsed after maintaining CR for over 7 years.